Prediction of Urosepsis after Percutaneous Nephrolithotomy using Neutrophil-Lymphocyte Ratio - Lacoul, Robal; Luitel, Bhojraj; Chapagain, Suman; Poudyal, Sujeet; Pradhan, Manish Man; Chalise, Pawan Raj (Journal of Institute of Medicine Nepal, 2025)
Introduction: Percutaneous nephrolithotomy (PCNL) is the preferred modality treatment for kidney stones >2 cm. Prediction of postoperative infection remains a major concern. The neutrophil-to-lymphocyte ratio (NLR) is an inexpensive and readily available marker of systemic inflammation and has shown potential in predicting infection and sepsis. This study aims to investigate the utility of preoperative NLR in predicting urosepsis following PCNL. Methods: A prospective observational study was conducted on 86 patients undergoing PCNL at Maharajgunj Medical Campus, Institute of Medicine, Tribhuvan University, Nepal. Preoperative NLR was calculated from complete blood counts. Postoperative infectious outcomes were analyzed, logistic regression and receiver operating characteristic (ROC) curve analyses were performed to assess NLR’s predictive value. Results: Post-PCNL fever occurred in 43 patients (50%) and sepsis in 16 patients (18.6%). Patients with sepsis had significantly higher preoperative NLR (3.55 ± 2.25 vs. 1.82 ± 0.68, p < 0.001). An NLR cut-off of 1.86 predicted sepsis with area under curve (AUC) 0.829, 93.8% sensitivity and 68.6% specificity (p < 0.001). Higher risk of sepsis was seen in patients with chronic kidney disease (37.5%), preoperative percutaneous nephrostomy (46.7%), prior UTI admission (30.3%), staghorn stones (50%), longer operative time (99.69 ± 31.12 vs 78.26 ± 34.23 minutes). Conclusion: Preoperative NLR may be a useful marker for identifying patients at increased risk of sepsis after PCNL, particularly in patients with complex stones and value >1.86. Further large-scale studies are needed to validate its role and compare it with other established biomarkers.